STRATEGY AND NEGOTIATION TACTICS BLIMBING MARKET TRADERS âMANDIRIâ GROUP (P3B âMANDIRIâ) MALANG, EAST JAVA - Krisdianto, Dadang; Nikin, Ratna (Departemen Ilmu Administrasi Bisnis, Fakultas Ilmu Sosial dan Ilmu Politik, UNPAD, 2017)
ABSTRACTThis study discusses how the strategy and tactics of negotiation Blimbing market traders joined in Blimbing Market Traders Association